Primary Pituitary Abscess: Two Case Reports - Ghosh, Sayak R.; Pecorari, Isabella L.; Funari, Abigail; Ledet, Alexander J.; Lally, Anne; Karandish, Alireza; Agarwal, Vijay (Journal of Neurological Surgery Reports, 2024)
Introduction Pituitary abscess is a rare disorder that represents a small fraction of all pituitary lesions. In this report, we present two additional cases with unique features to promote awareness and prompt surgical intervention.Case Presentations A 42-year-old male presented with headache, photophobia, subjective fever, dizziness, imbalance, nausea, and vomiting. A pituitary hormone panel confirmed hypothyroidism and suggested central hypogonadism and secondary adrenal insufficiency. Magnetic resonance imaging (MRI) showed a large sellar mass measuring 2.5 cm × 1.8 cm × 1.6 cm (CC × XT × AP). A 76-year-old woman presented with several months of headaches and unsteady gait in the setting of a known previously asymptomatic sellar lesion, measuring 1.8 cm × 1.2 cm × 1.5 cm (XT × CC × AP). Repeat MRI demonstrated possible hemorrhage within the lesion. In both cases, a preliminary diagnosis of pituitary macroadenoma was made, but transsphenoidal surgery revealed an encapsulated abscess; cultures obtained from the abscesses stained for gram-positive bacteria.Conclusion Pituitary abscess is a rare, potentially life-threatening disorder that may be easily mistaken for other sellar lesions. In this review, we contribute two additional cases of pituitary abscesses to increase awareness and emphasize the importance of proper diagnosis and management.
Keywords: pituitary abscess; sellar lesions; hypopituitarism; case reports